In situ polymerization of ethylene with bis(imino)pyridine iron(II) catalysts supported on clay: the synthesis and characterization of polyethylene-clay nanocomposites - Ray, S; Galgali, G; Lele, Arundhati C.; Sivaram, S (Journal of Polymer Science Part A-Polymer Chemistry, 2005)
Polyethylene-clay nanocomposites were synthesized by in situ polymerization with 2,6-bis[1-(2,6-diisopropylphenylimino)ethyl] pyridine iron(II) dichloride supported on a modified montmorillonite clay pretreated with methylaluminoxane (MAO). The catalysts and the obtained nanocomposites were examined with wide-angle X-ray scattering. The exfoliation of the clay was further established by transmission electron microscopy. Upon the treatment of the clay with MAO, there was an increase in the d-spacing of the clay galleries. No further increase in the d-spacing of the galleries was observed with the iron catalyst supported on the MAO-treated clay. The catalyst activity for ethylene polymerization was independent of the Al/Fe ratio. The exfoliation of the clay inside the polymer matrix depended on various parameters, such as the clay content, catalyst content, and Al/Fe ratio. The crystallinity percentage and crystallite size of the nanocomposites were affected by the degree of exfoliation of the clay. Moreover, when ethylene was polymerized with a mixture of the homogeneous iron(II) catalyst and clay, the degree of exfoliation was significantly lower than when the polymerization was performed with a preformed clay-supported catalyst. This observation suggested that in the supported catalyst, at least some of the active centers resided within the galleries of the clay. (C) 2004 Wiley Periodicals, Inc.
Keywords: clay; In situ polymerization; Nanocomposites; polyethylene (PE); TEM; WAXS